2022
DOI: 10.3390/ijms23105433
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phytohormones and Transcriptomic Profiling of the Female and Male Inflorescence Development in Manchurian Walnut (Juglans mandshurica Maxim.)

Abstract: Flowers are imperative reproductive organs and play a key role in the propagation of offspring, along with the generation of several metabolic products in flowering plants. In Juglans mandshurica, the number and development of flowers directly affect the fruit yield and subsequently its commercial value. However, owing to the lack of genetic information, there are few studies on the reproductive biology of Juglans mandshurica, and the molecular regulatory mechanisms underlying the development of female and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…While leafing date was not a significant predictor, we note that the slope estimate is in the expected direction. Notably, the earliest leafing protogynous varieties have catkin buds roughly of similar size to the latest leafing protandrous varieties.
Figure S10: Reanalysis of RNA-seq experiment from Li et al . (2022b).
…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…While leafing date was not a significant predictor, we note that the slope estimate is in the expected direction. Notably, the earliest leafing protogynous varieties have catkin buds roughly of similar size to the latest leafing protandrous varieties.
Figure S10: Reanalysis of RNA-seq experiment from Li et al . (2022b).
…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…TPP genes were recently identified as differentially expressed across the transition to flowering in both J. sigillata and J. mandshurica (Lu et al . 2020; Li et al . 2022b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is feasible to mine sex determination genes in S. chinensis using RNA-sequencing. It has also been shown that transcription factors, such as WRKY, MYB, and bHLH may play crucial roles in plant sex determination [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%